Helical tomotherapy to LINAC plan conversion utilizing RayStation Fallback planning. (January 2017) - Zhang, Xin; Penagaricano, Jose; Narayanasamy, Ganesh; Corry, Peter; Liu, TianXiao; Sanjay, Maraboyina; Paudel, Nava; Morrill, Steven
Abstract: RaySearch RayStation Fallback (FB) planning module can generate an equivalent backup radiotherapy treatment plan facilitating treatment on other linear accelerators. FB plans were generated from the RayStation FB module by simulating the original plan target and organ at risk (OAR) dose distribution and delivered in various backup linear accelerators. In this study, helical tomotherapy (HT) backup plans used in Varian TrueBeam linear accelerator were generated with the RayStation FB module. About 30 patients, 10 with lung cancer, 10 with head and neck (HN) cancer, and 10 with prostate cancer, who were treated with HT, were included in this study. Intensity‐modulated radiotherapy Fallback plans (FB‐IMRT) were generated for all patients, and three‐dimensional conformal radiotherapy Fallback plans (FB‐3D) were only generated for lung cancer patients. Dosimetric comparison study evaluated FB plans based on dose coverage to 95% of the PTV volume (R95 ), PTV mean dose (D mean ), Paddick's conformity index (CI), and dose homogeneity index (HI). The evaluation results showed that all IMRT plans were statistically comparable between HT and FB‐IMRT plans except that PTV HI was worse in prostate, and PTV R95 and HI were worse in HN multitarget plans for FB‐IMRT plans. For 3D lung cancer plans, only the PTV R95 was statistically comparable between HT and FB‐3D plans, PTV Dmean was higher, and CI and HI were worse compared to HT plans. The FB plans using a TrueBeam linear accelerator generally offer better OAR sparing compared to HT plans for all the patients. In this study, all cases of FB‐IMRT plans and 9/10 cases of FB‐3D plans were clinically acceptable without further modification and optimization once the FB plans were generated. However, the statistical differences between HT and FB‐IMRT/3D plans might not be of any clinically significant. One FB‐3D plan failed to simulate the original plan without further optimization.